BUSINESS INTELLIGENCE DEVELOPMENT MODEL USING STAR SCHEMA METHODOLOGY - Henderi Henderi; Indri Handayani; Meta Amalia Dewi (Universitas Raharja, 2012)
Nowdays, implemented the information systems that are integrated to business processes in the organization has become a primary necessity. Information systems in the organization are mostly used to assist the implementation of enterprise business process. In the generally, the systems have not been able to provide strategic information and assist management for evaluating of the enterprise’s performance. This problems occurs because the most of the information system is built using the data warehouse concept. This problem occurs also in the information system in most universities in the city of Tangerang as the study sample. The solutions for this problem is build information systems that apply the concepts and ways of working with business intelligence using star schema methodologies that can be presented as an enterprise’s performance measurement tools. Business intelligence can also be used as a basis in conducting surveillance for business intelligence can also provide: 1. early information (alert) if there are deviations between performance with a pre-determined goals, 2. Provided a report was automation (automated-feedback), 3. Memonitoring to key performance index (KPI) in real-time. The system development methodology in this reseach using the star schema. Through this approach created an information system with the concept of business intellegence with star schemas methologies that can produce information that is strategic, as needed, and as tools implement enterprise performance measurement. The end result of research is a business intelligence system with a star schema as enterprise performance measurement tools on Higher Education Raharja as a prototype implementation.